PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DENGAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL PADA MATERI PENINGGALAN SEJARAH KERAJAAN BUDDHA DI INDONESIA - Sutisna, Mamur; Robiatul Ulumiah, Ai (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
This study aims to improve students' motivation and learning outcomes through learning Social Scienceby applying the model of Problem Based Learning. This research is motivated by the problems that occur in the classroom, namely the lack of motivation and student learning outcomes. The design of this study used a classroom action research model consisting of three cycles, each cycle conducted in two meetings, including the planning stage, action implementation, interview observation, documentation, analysis and reflection. The results showed that through the application of Probem Based Learning model can improve the motivation and learning outcomes of students with Social Sciencelearning on the material of the historical relics of the Buddhist kingdom in Indonesia. This can be seen from the results of observation and analysis which shows that the assessment of RPP cycle I reached the percentage of 67.5% enough category, cycle II reached the percentage of 77.5% good category, cycle III reached the percentage of 90% very good category. Implementation of learning in the first cycle reached the percentage of 62.9% enough category, cycle II reached the percentage of 77.5% good category, cycle III reached the percentage of 90% very good category. While the results of students' learning motivation cycle I reached the percentage of 65% enough category, cycle II reached the percentage of 75.7% good category, cycle III reached the percentage of 88% very good category. Similarly, the results of student learning that meets the value of KKM in cycle I reached the percentage of 59% enough category, cycle II reached the percentage of 73% good category, cycle III reached the percentage of 90% very good category. Classroom action research ends in cycle III because the aspects studied are considered to have succeeded in achieving the indicator of achievement determined. This is because the model of Problem Based Learning is the appropriate learning resources for student development in Social Sciencelearning related to daily life. Based on the above description, it can be concluded that the model of Problem Based Learning can improve the motivation and student learning outcomes with Social Sciencelearning on the material of the historical relics of the Buddhist kingdom in Indonesia.